Testosterone, Sex Hormone-Binding Globulin and the Metabolic Syndrome in Men: An Individual Participant Data Meta-Analysis of Observational Studies - Brand, Judith S.; Rovers, Maroeska M.; Yeap, Bu B.; Schneider, Harald J.; Tuomainen, Tomi-Pekka; Haring, Robin; Corona, Giovanni; Onat, Altan; Maggio, Marcello; Bouchard, Claude; Tong, Peter C. Y.; Chen, Richard Y. T.; et al. (PloS one, 2014)
Low total testosterone (TT) and sex hormone-binding globulin (SHBG) concentrations have been associated with the metabolic syndrome (MetS) in men, but the reported strength of association varies considerably. We aimed to investigate whether associations differ across specific subgroups (according to age and body mass index (BMI)) and individual MetS components. Two previously published meta-analyses including an updated systematic search in PubMed and EMBASE. Cross-sectional or prospective observational studies with data on TT and/or SHBG concentrations in combination with MetS in men. We conducted an individual participant data meta-analysis of 20 observational studies. Mixed effects models were used to assess cross-sectional and prospective associations of TT, SHBG and free testosterone (FT) with MetS and its individual components. Multivariable adjusted odds ratios (ORs) and hazard ratios (HRs) were calculated and effect modification by age and BMI was studied. Men with low concentrations of TT, SHBG or FT were more likely to have prevalent MetS (ORs per quartile decrease were 1.69 (95% CI 1.60-1.77), 1.73 (95% CI 1.62-1.85) and 1.46 (95% CI 1.36-1.57) for TT, SHBG and FT, respectively) and incident MetS (HRs per quartile decrease were 1.25 (95% CI 1.16-1.36), 1.44 (95% 1.30-1.60) and 1.14 (95% 1.01-1.28) for TT, SHBG and FT, respectively). Overall, the magnitude of associations was largest in non-overweight men and varied across individual components: stronger associations were observed with hypertriglyceridemia, abdominal obesity and hyperglycaemia and associations were weakest for hypertension. Associations of testosterone and SHBG with MetS vary according to BMI and individual MetS components. These findings provide further insights into the pathophysiological mechanisms linking low testosterone and SHBG concentrations to cardiometabolic risk.